Positive electrode with high carrier mobility and application

By adding high carrier mobility materials as functional additives to the positive electrode of the secondary battery, the electrochemical inertia problem of positive electrode active materials is solved, and the utilization rate of active substances and battery performance are improved.

CN119581482APending Publication Date: 2025-03-07GUANGDONG HENGQIN YANPO ENERGY TECHNOLOGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411721159.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The positive electrode active material in secondary batteries is electrochemically inert, which makes it difficult to fully utilize the active material and affects the performance of the battery.

Method used

A material with high carrier mobility is added to the positive electrode as a functional additive, such as Li(1-x)NxAlO2 oxide or Li2MTiO4, and heterogeneous elements are introduced into the inorganic compound-based solid electrolyte or a material that promotes carrier migration is added.

Benefits of technology

By improving carrier migration performance, improving the utilization rate of active substances, reducing the loss of active substances, enhancing the redox reaction kinetics of the battery, extending the battery life and improving energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581482A_ABST
    Figure CN119581482A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode with high carrier mobility and application, and belongs to the field of electrochemistry. The positive electrode contains an active substance, a conductive carbon material, a binder and a functional additive with high carrier mobility, the functional additive is a first functional additive or a second functional additive, the first functional additive is Li (1-x) NxAlO2 oxide without electrochemical activity, x is greater than or equal to 0 and less than or equal to 1, N is Na, K or Si, and x is greater than or equal to 0 and less than or equal to 1. The second functional additive is an inorganic compound which is different from the active substance and has electrochemical activity. The positive electrode prepared by the invention can promote the migration of carriers during the operation of the battery, improve the redox reaction kinetics of the battery and reduce the loss of active substances during the operation of the battery, so that a high-performance secondary battery can be constructed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrochemistry, and in particular to a positive electrode with high carrier mobility and application thereof in a secondary battery. Background Art

[0002] At present, the surge in energy demand has led to the depletion of fossil fuels and increased environmental pollution, which seriously hinders green and sustainable development. Therefore, renewable energy such as solar energy, wind energy, geothermal energy and tidal energy have been widely recognized worldwide for their environmental protection and carbon reduction potential. These energy sources can not only alleviate energy shortages, but also reduce carbon footprints and harmful emissions, which is crucial to environmental protection. However, renewable energy depends on natural conditions, and there are problems with unstable supply and storage. To solve these problems, scientific research and industry are actively seeking efficient and low-cost energy storage solutions to stabilize the supply of renewable energy. Building a green and reliable energy storage system has become the key to achieving low-carbon environmental protection and sustainable development. Therefore, it is urgent to develop high-efficiency, economical and advanced energy storage devices to improve energy storage efficiency and life, reduce costs, ensure their popularization and application, and provide support for building a clean, low-carbon, safe and efficient energy system.

[0003] Lithium metal has a high theoretical specific capacity (3860 mAh g –1 ), low redox potential (-3.04 V vs. standard hydrogen electrode) and low density (0.534 g cm –3) is considered to be an ideal negative electrode material (see: Yuping Wu et al., Sustainable release of Mg(NO3)2from a separator boosts the electrochemical performance of lithium metal as an anode for secondary batteries, Energy & Environmental Science, Vol. 17, 2024, 5461), making metal lithium secondary batteries very likely to become the next generation of commercial batteries. Today, the application range of lithium-ion batteries has been widely expanded to many fields such as portable electronic devices, electric vehicles and even large-scale energy storage systems, and its influence is far-reaching and extensive (see: Wu Yuping. Lithium-ion Batteries: Applications and Practices [M]. Second Edition. Beijing: Chemical Industry Press, 2012). The unique embedding mechanism of lithium-ion batteries brings advantages such as low self-discharge, no memory effect, easy operation and reliable performance, which establishes its core position in the field of energy storage. In addition, the introduction of new batteries such as sodium and potassium has broadened the selection range of negative electrode materials for secondary batteries, and can also solve the problem of limited lithium resources. However, the problem of electrochemical inertness of the active materials of secondary batteries has always plagued researchers. For example, the conductivity of sulfur itself in lithium-sulfur batteries is only 5×10 -30 S cm -1 Such low conductivity will inevitably make it difficult for active sulfur substances to be fully utilized, thus affecting battery performance.

[0004] In order to solve the above problems existing in secondary batteries, the existing technology adopts the method of adding carbon materials with good conductivity into the active materials for the positive electrode of secondary batteries, which can compensate for the electrochemical inertness of the active materials themselves to a certain extent. However, the introduction of carbon materials cannot completely suppress the loss of active materials. High-performance positive electrodes still need to be explored to ensure the commercial application of secondary batteries.

[0005] Adding inorganic compound-based solid electrolytes (LFP, LCO, LMO, etc.) to the positive electrode can effectively improve its performance. However, the ionic conductivity of inorganic compound-based solid electrolytes themselves is limited, which makes it difficult to maximize the use of active materials. Summary of the invention

[0006] The purpose of the present invention is to address the deficiencies of the prior art and propose a positive electrode with high carrier mobility, which effectively improves the utilization rate of the positive electrode active material by adding high carrier mobility materials, thereby limiting the active material to the positive electrode side and reducing the loss of active material.

[0007] To achieve the above object, the present invention adopts the following technical solution: In a first aspect, the present invention provides a positive electrode with high carrier mobility, wherein the positive electrode contains an active material, a conductive carbon material, a binder and a functional additive with high carrier mobility, wherein the functional additive is a first functional additive or a second functional additive; The first functional additive is a Li-ion-free material that is electrochemically inactive (i.e., does not undergo reversible insertion / deinsertion of lithium ions). (1-x) N x AlO2 oxide (0≤x≤1, N=Na, K or Si); The second functional additive is an inorganic compound having electrochemical activity and different from the active material.

[0008] Furthermore, the second functional additive is Li2MTiO4 (M=Mn, Fe or Ni), Li3VO4, LiV2O4, LiV3O8, NaV3O8, NaMnO2, Na4CoO4, NaCo2O4, NaCoO2, Li x R y One or more of FePO4 (R = Na, Ni, Co or Mn, x>0, y>0), NaFePO4, VOPO4, Li3VPO4, LiTi2(PO4)3, Li2Ti(PO4)2, LiFeSO4F, LiQBO3 and Li2QSiO4 (Q = Mn, Fe, Co or Ni).

[0009] Furthermore, the functional additive is a third functional additive, and the third functional additive is a substance formed by doping the first functional additive or the second functional additive with heterogeneous ions or atoms, or a substance formed by coating the first functional additive or the second functional additive with heterogeneous materials, or a mixture formed by direct physical mixing (such as grinding, ball milling, etc.) of the first functional additive or the second functional additive with heterogeneous materials, or a mixture of two or more first functional additives, or a mixture of two or more second functional additives.

[0010] Among them, the heterogeneous ions or atoms can be one or more of Na, K, Li, Mg, Si, S, Se, N, Ti, Fe, Co, Ni, Mn, In, Cu, Au, Ag, Zn, Sn, N, F, P, Mo, W, Pt, Cd, B, C, Cl, V, etc.

[0011] The heterogeneous materials include, but are not limited to, oxides, sulfides, nitrides, various forms of carbon-based materials or conductive polymer materials and other materials with good electronic conductivity and ionic conductivity.

[0012] Furthermore, the content of the functional additive in the positive electrode is 1-40 wt.%, preferably 2-10 wt.%.

[0013] Furthermore, the particle size of the functional additive is 1 nm-40 μm, preferably 1 nm-10 μm, and more preferably 1 nm-2 μm.

[0014] Furthermore, the active material is one of sulfur, selenium powder, lithium salt, sodium salt, potassium salt or ternary material, and the content of the active material in the positive electrode is greater than 50 wt.%, wherein the lithium salt is selected from lithium cobalt oxide, lithium manganese oxide, lithium titanate or lithium iron phosphate.

[0015] The sodium salt is selected from NASICON type polyanion compounds (Na3V2(PO4)3), Prussian blue compounds, tunnel oxides or layered oxides.

[0016] The potassium salt is selected from layered transition metal oxides, polyanionic materials, Prussian blue analogs or organic cathode materials.

[0017] The ternary material is Ni x Co y Mn z O2 or Ni x Co y Al z O2, x>0, y>0, z>0.

[0018] Furthermore, the binder is one or more of a fluoroolefin polymer (such as polyvinylidene fluoride (PVDF)), an acrylate polymer, an epoxy polymer, an acrylonitrile polymer, butyl rubber or cellulose, and the content of the binder in the positive electrode is 1-15 wt.%.

[0019] In a second aspect, the present invention provides the use of the aforementioned positive electrode with high carrier mobility in an electrochemical energy storage device, wherein the electrochemical energy storage device is a secondary battery.

[0020] Furthermore, the secondary battery is a high energy density lithium ion battery, a metal lithium secondary battery (such as a lithium sulfur battery), a sodium ion battery or a potassium ion battery.

[0021] Furthermore, the separator of the secondary battery is one of a polymer membrane, a modified membrane, and a solid membrane; the negative electrode active material of the secondary battery is one of lithium (sodium, potassium) powder, lithium (sodium, potassium) sheet, lithium (sodium, potassium) bar or lithium (sodium, potassium) foil; and the electrolyte of the secondary battery is a salt-containing organic solvent.

[0022] Compared with the prior art, the present invention has the following beneficial effects: The present invention starts from the perspective of positive electrode modification, and improves their electrochemical activity by introducing impurity elements or adding materials that can promote carrier migration into inorganic compound-based solid electrolytes, thereby preparing secondary battery positive electrode modification materials with good carrier migration performance, thereby constructing high-performance secondary batteries. This method is simple and efficient. The positive electrode solves the following problems existing in secondary batteries: the positive electrode active materials in secondary batteries have certain electrochemical inertness and cannot be fully utilized. Taking metal-sulfur batteries as an example, the conductivity of elemental sulfur itself is extremely low, so that in the process of preparing sulfur positive electrodes, a certain amount of carbon materials with excellent conductivity are often added to improve the utilization rate of sulfur. However, this improvement is very limited. Therefore, the prior art proposes to add additives with good polarity or ionic (electronic) conductivity to the positive electrode to further compensate for the electrochemical inertness of the active substance itself. However, the additives proposed at this stage have limited ionic conductivity and cannot play the role of the active substance to a greater extent.

[0023] The present invention adopts an inorganic compound doped with higher ionic conductivity or a material capable of promoting carrier migration as a functional additive for the positive electrode to construct a positive electrode for a secondary battery with high carrier mobility. The positive electrode can promote the migration of carriers during the operation of the battery, improve the redox reaction kinetics of the battery, thereby effectively improving the utilization rate of the active material, limiting the active material to the positive electrode side, and reducing the loss of the active material during the operation of the battery. This method can break through the limitations of traditional inorganic compound-based solid electrolytes as positive electrode additives, and also broaden the selection range of secondary battery positive electrode functional additive materials. In addition, the positive electrode with high carrier mobility of the present invention also has the advantages of simple preparation process and storage conditions, and has the potential for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A schematic diagram of the role of the positive electrode prepared by the present invention in a high energy density secondary battery; Figure 2 This is a scanning electron microscope image of the LNFP@CS-5 positive electrode prepared in Example 2; Figure 3 This is the electrochemical impedance spectrum of the pure LNFP sheet prepared in Example 2 in a stainless steel symmetric battery; Figure 4 The cycling performance diagram of the LNFP@CS-5 cathode prepared in Example 2 in a lithium-sulfur battery (electrolyte content: 50 μL); Figure 5 This is the rate performance diagram of the LNFP@CS-5 cathode prepared in Example 2 in a lithium-sulfur battery (electrolyte content: 50 μL); Figure 6 The charge and discharge curve of the LNFP@CS-5 cathode prepared in Example 2 in a lithium-sulfur battery (electrolyte content: 50 μL); Figure 7 Schematic diagram of the linear sweep voltammetry curve of the LNFP@CS-5 cathode prepared in Example 2 in a lithium-sulfur battery (electrolyte content: 50 μL); Figure 8 This is the AC impedance spectrum of the LNFP@CS-5 positive electrode prepared in Example 2 in a lithium-sulfur battery (electrolyte content: 50 μL). DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with specific examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention.

[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the examples can be obtained from the market or other existing feasible methods.

[0027] In the electrochemical tests of the following examples, the tests of the AC impedance spectra, cyclic voltammetry linear spectra, rate performance and cycle performance of different positive electrodes were all carried out by using a CHI760E electrochemical workstation and a LAND battery testing system.

[0028] (1) Conductivity is obtained through electrochemical impedance spectroscopy: The test battery uses a stainless steel (SS) / pure additive material sheet / stainless steel (SS) battery system. Electrochemical impedance spectroscopy is performed at a temperature gradient ranging from 25°C to 75°C, with an AC voltage amplitude of 5 mV and a frequency range of 0.1 Hz to 100 kHz to obtain ionic conductivity.

[0029] (2) In a CR2025 battery case, the positive electrode is a carbon-sulfur composite material containing different additives, the negative electrode is a lithium sheet, and the separator is a commercial separator for secondary batteries (DKJ-14). The applied voltage amplitude is 5 mV, and the electrochemical AC impedance spectroscopy test is performed in the frequency range of 0.01 Hz to 100 kHz.

[0030] (3) Linear sweep voltammetry is used to determine the utilization rate of active sulfur materials by different separators. The positive electrode is a carbon-sulfur composite material containing different additives, and the negative electrode is a lithium sheet. The scanning range is 1.8~2.8 V, and the scanning speed is 0.1 mV / s.

[0031] (4) In the examples of the present invention, the rate performance charge and discharge tests of button cells assembled with positive electrodes containing different additives were all conducted using the LAND battery test system. The battery charge and discharge voltage range was 1.8 to 2.8 V. In the rate performance, the applied current densities were 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C, and 3 C, respectively. Long cycle tests were conducted at a current density of 1 C.

[0032] Example 1

[0033] The material selected as the positive electrode additive in this embodiment is lithium sodium iron phosphate (Li 0.95 Na 0.05 FePO4, LNFP).

[0034] The preparation process of LNFP provided in this embodiment is as follows: 9.0 g of ferrous oxalate (FeC2O4·2H2O), 9.0 g of ammonium dihydrogen phosphate (NH4H2PO4), 0.13 g of sodium carbonate (Na2CO3) and 1.8 g of lithium carbonate (Li2CO3) were mixed uniformly, then calcined at 350 °C for 5 h, and then calcined at 700 °C. The obtained product was washed and dried to obtain LNFP powder.

[0035] Pure LNFP powder was pressed into pure LNFP sheets at a certain pressure and then assembled into a stainless steel symmetrical battery (SS / / SS), in which the positive and negative electrodes were both made of stainless steel and pure LNFP was sandwiched between the positive and negative electrodes. The ionic conductivity of pure LNFP can be calculated by testing the obtained SS / / SS battery, and the results are shown in Table 1.

[0036] The carbon-sulfur composite material, conductive carbon (Super P) and binder (polyvinylidene fluoride, PVDF) were mixed evenly in a mass ratio of 80 wt%: 10 wt%: 10 wt%, and then LNFP was added, and then a certain amount of N -methylpyrrolidone (NMP), stirred to form a uniform slurry, and then coated on aluminum foil. After drying and cutting, a sulfur positive electrode with LNFP added was obtained, wherein the content of LNFP was 10 wt%. The positive electrode was recorded as LNFP@CS-10. The relevant performance test data of the prepared LNFP@CS-10 in lithium-sulfur batteries are summarized in Table 1. Among them, 1C=1675mAhg -1 .

[0037] Taking Example 1 as an example, the role of the positive electrode prepared by the present invention in a high energy density secondary battery is as follows: Figure 1 As shown. Since additives with high carrier mobility are added to the positive electrode, they can promote the redox reaction inside the battery, making the battery have excellent utilization of active materials.

[0038] Example 2

[0039] In this embodiment, the content of the high carrier additive (LNFP) used for the positive electrode is 5 wt%, and the positive electrode is recorded as LNFP@CS-5. Other parameters and processes are the same as those in Example 1. The relevant performance test data obtained are summarized in Table 1.

[0040] Figure 2 This is a scanning electron microscope image of the LNFP@CS-5 positive electrode prepared in Example 2.

[0041] Figure 3 This is the electrochemical impedance spectroscopy (EIS) of the pure LNFP sheet prepared in Example 2 in a stainless steel symmetric cell. The calculated ionic conductivity of LNFP at 25 °C is 8.8 mS cm -1 , the doping of sodium ions helps the transport of active cations.

[0042] Figure 4 and Figure 5 The cycle performance and rate performance diagrams of the LNFP@CS-5 cathode prepared in Example 2 in a lithium-sulfur battery (electrolyte content: 50 μL) are shown in Figure 2. It can be seen from the cycle performance diagram that the initial discharge capacity of the prepared lithium-sulfur battery is as high as 1152 mAh g -1 , and can cycle 500 times, with a capacity decay of only 0.08% per cycle, indicating that LNFP can limit the active sulfur substances on the positive electrode side, reduce the loss of active sulfur substances, and maintain its high utilization rate. In addition, the coulombic efficiency of each cycle of the battery is greater than 99%, indicating that the addition of LNFP can enable the battery to maintain good electrochemical behavior. It can be seen from the rate performance diagram that the lithium-sulfur battery prepared at different current densities has a higher discharge specific capacity, indicating that the doping of LNFP can make the battery have excellent rate performance.

[0043] Figure 6 This is the charge and discharge curve of the LNFP@CS-5 positive electrode prepared in Example 2 in a lithium-sulfur battery (electrolyte content: 50 μL). In the figure, an obvious charge and discharge platform can be seen, and the distance between the charge curve and the discharge curve is small, indicating that the polarization of the battery is small.

[0044] Figure 7 and Figure 8 They are respectively a schematic diagram of the linear sweep voltammetry curve and an AC impedance spectrum of the LNFP@CS-5 positive electrode prepared in Example 2 in a lithium-sulfur battery (electrolyte content: 50 μL). The cyclic voltammetry curves of the first three cycles have good overlap and the battery shows a low charge transfer impedance, indicating that LNFP can improve the utilization rate of active sulfur substances.

[0045] Example 3

[0046] In this embodiment, the content of the high carrier additive (LNFP) used for the positive electrode is 3 wt%, and the positive electrode is recorded as LNFP@CS-3. Other parameters and processes are the same as those in Example 1. The relevant performance test data obtained are summarized in Table 1.

[0047] Example 4

[0048] The material selected as the positive electrode functional additive in this embodiment is lithium sodium aluminate (Li 0.95 Na 0.05 AlO2, LNAO), its content in the positive electrode is 5 wt%, and the positive electrode is denoted as LNAO@CS-5.

[0049] The pure LNAO powder was pressed into pure LNAO sheets at a certain pressure and then assembled into a stainless steel symmetric battery (SS / / SS), in which the positive and negative electrodes were both stainless steel, and pure LNAO was sandwiched between the positive and negative electrodes. The ionic conductivity of pure LNAO can be calculated by testing the obtained SS / / SS battery, and the results are shown in Table 1.

[0050] Other parameters and processes are the same as those in Example 1. The relevant performance test data obtained are summarized in Table 1.

[0051] Example 5

[0052] In this embodiment, the positive electrode functional additive lithium sodium iron phosphate (LNFP) proposed in Example 1 is used in a lithium selenium (Li / / Se) battery.

[0053] Selenium (Se) powder, Super P and PVDF were mixed evenly in a mass ratio of 80 wt%: 10 wt%: 10wt%, and then LNFP was added. N -methylpyrrolidone (NMP), stirred to form a uniform slurry, and then coated on aluminum foil. After drying and cutting, a selenium positive electrode with LNFP added was obtained, in which the content of LNFP was 5wt%, and the positive electrode was recorded as LNFP@CSe-5. The relevant performance test data of the prepared LNFP@CSe-5 in lithium selenium batteries are summarized in Table 1. Among them, 1C=675mAhg -1 .

[0054] Example 6

[0055] The material selected as the positive electrode functional additive in this embodiment is lithium sodium aluminate (Li 0.95 Na 0.05 AlO2, LNAO), the content of which in the positive electrode is 5 wt%, and the positive electrode is recorded as LNAO@CSe-5. Other parameters and processes are the same as those in Example 5. The relevant performance test data obtained are summarized in Table 1.

[0056] Example 7

[0057] In this embodiment, the high-carrier positive electrode additive lithium sodium iron phosphate (LiFePO4) mentioned in Example 1 is added to the 0.95 Na 0.05 FePO4, LNFP) are used in sodium-ion batteries.

[0058] In this embodiment, the electrode materials were assembled into half-cells in a button-type battery case (CR2025 type) in an argon-filled glove box for testing. The positive electrode was the prepared electrode sheet, the counter electrode was a metal sodium sheet (diameter 16 mm) with a diameter of 16 mm, and the electrolyte consisted of 1.0 M NaClO4 and EC / PC solution (1:1, V / V). 50 μL of electrolyte was added to each button-type battery. After the components were assembled in order, they were packaged.

[0059] The positive electrode sheet and preparation process are as follows: Na3V2(PO4)3 (NVP), PVDF and Super P were mixed in a mass ratio of 80 wt%:10 wt%:10wt%, and LNFP was added. N -methyl pyrrolidone solvent and stirred to obtain slurry, which was then coated on the surface of aluminum foil and dried in vacuum at 80°C before cutting to obtain positive electrode sheets. The content of LNFP was 5wt%, and the positive electrode was named LNFP@Na-5. The obtained LNFP@Na-5 was cycled at a charge and discharge rate of 1 C (1C=138mAhg -1 ), and the relevant electrochemical data are summarized in Table 1.

[0060] Example 8

[0061] The material selected as the positive electrode functional additive in this embodiment is lithium sodium aluminate (Li 0.95 Na 0.05 AlO2, LNAO), the content of which in the positive electrode is 5 wt%, and the positive electrode is recorded as LNAO@Na-5. Other parameters and processes are the same as those in Example 7. The relevant performance test data obtained are summarized in Table 1.

[0062] Table 1 Electrochemical performance of different positive electrodes prepared in Examples 1-8 in different secondary batteries

[0063] Comparative Example 1

[0064] In this comparative example, the positive electrode of the lithium-sulfur battery is a carbon-sulfur composite electrode, the negative electrode is metallic lithium, and the separator is a commercial separator (DKJ-14). The raw materials and preparation process of the positive electrode are as follows: The active substances sublimed sulfur and Super P were put into a ball mill at a mass ratio of 60wt.%:40wt.% and ball-milled at a speed of 400rpm / min for 10 hours, and then the mixed powder was put into a hydrothermal kettle and kept at 155°C for 8 hours.

[0065] The hydrothermal mixed powder was fully stirred in N-methylpyrrolidone solvent to obtain a slurry, which was then coated on the surface of aluminum foil and cut to obtain a positive electrode sheet after vacuum drying at 80°C. The carbon-sulfur positive electrode sheet was transferred to a glove box and packaged into a button battery mold (CR2025) with a diaphragm and a lithium negative electrode, and sealed under pressure to obtain a lithium-sulfur battery. Electrochemical tests were also performed, and the relevant electrochemical data are summarized in Table 2.

[0066] Comparative Example 2

[0067] In this comparative example, the positive electrode of the metal lithium secondary battery is a carbon-selenium composite electrode, and the negative electrode is metal lithium.

[0068] The carbon-selenium positive electrode, separator, and metallic lithium were packaged in a CR2025 battery case in order. The electrolyte was dripped on both sides of the separator. -2 The battery was packaged with a force of 100° and then tested on the LAND battery test system after standing for 24 h. The battery was cycled at a charge and discharge rate of 1 C, and the relevant electrochemical data are summarized in Table 2.

[0069] Comparative Example 3

[0070] In this comparative example, the positive electrode of the secondary battery is an NVP positive electrode, and the specific assembly process of the battery is as follows: In a glove box filled with argon, the NVP positive electrode, DKJ-14, and sodium sheet were packaged in a CR2025 battery case in order. The electrolyte used was 1.0 M NaClO4 and EC / PC solution (1:1, V / V), which were dripped on both sides of the diaphragm and heated in a packaging machine at 500 kg cm -2 The battery was packaged with a force of 100° and then tested on the LAND test equipment after standing for 24 h. The battery was cycled at a charge and discharge rate of 1 C, and the relevant electrochemical data are summarized in Table 2.

[0071] Table 2 Electrochemical performance of the positive electrode assembled into the battery in Comparative Examples 1-3

[0072] It can be found from Table 1 and Table 2 that the battery made of the positive electrode without adding functional additives has a large capacity decay per cycle and a short cycle number. The battery made of the positive electrode with functional additives has a greatly reduced capacity decay per cycle and a significantly improved cycle number. These results show that the functional additives of the present invention can improve the redox reaction kinetics inside the battery, and further illustrate the superiority of the functional additives of the present invention in secondary batteries.

[0073] The present invention has been disclosed above with preferred embodiments, but they are not intended to limit the present invention. Any technical solutions obtained by adopting equivalent replacement or equivalent transformation solutions fall within the protection scope of the present invention.

Claims

1. A positive electrode with high carrier mobility, characterized in that: The positive electrode contains an active material, a conductive carbon material, a binder and a functional additive with high carrier mobility, wherein the functional additive is a first functional additive or a second functional additive, and the first functional additive is a Li (1-x) N x AlO2 oxide, 0≤x≤1, N=Na, K or Si, the second functional additive is an inorganic compound with electrochemical activity different from the active substance.

2. The positive electrode with high carrier mobility according to claim 1, characterized in that The second functional additive is Li2MTiO4, Li3VO4, LiV2O4, LiV3O8, NaV3O8, NaMnO2, Na4CoO4, NaCo2O4, NaCoO2, Li x R y One or more of FePO4, NaFePO4, VOPO4, Li3VPO4, LiTi2(PO4)3, Li2Ti(PO4)2, LiFeSO4F, LiQBO3 and Li2QSiO4; wherein in Li2MTiO4, M=Mn, Fe or Ni; Li x R y In FePO4, R = Na, Ni, Co or Mn, x>0, y>0; in LiQBO3 and Li2QSiO4, Q = Mn, Fe, Co or Ni.

3. The positive electrode with high carrier mobility according to claim 2, characterized in that: The functional additive is a third functional additive, and the third functional additive is a substance formed by doping the first functional additive or the second functional additive with heterogeneous ions or atoms, or a substance formed by coating the first functional additive or the second functional additive with heterogeneous materials, or a mixture formed by direct physical mixing of the first functional additive or the second functional additive with heterogeneous materials, or a mixture of two or more first functional additives, or a mixture of two or more second functional additives.

4. The positive electrode with high carrier mobility according to claim 1, characterized in that The content of the functional additive in the positive electrode is 1-40 wt.%.

5. The positive electrode with high carrier mobility according to claim 4, characterized in that The content of the functional additive in the positive electrode is 2-10 wt.%.

6. The positive electrode with high carrier mobility according to claim 1, characterized in that: The particle size of the functional additive is 1 nm-40 μm.

7. The positive electrode with high carrier mobility according to claim 1, characterized in that The active substance is one of sulfur, selenium powder, lithium salt, sodium salt, potassium salt or ternary material, and the content of the active substance in the positive electrode is greater than 50wt.%.

8. The positive electrode with high carrier mobility according to claim 1, characterized in that: The binder is one or more of fluoroolefin polymers, acrylate polymers, epoxy polymers, acrylonitrile polymers, butyl rubber or cellulose, and the content of the binder in the positive electrode is 1-15 wt.%.

9. Use of a positive electrode with high carrier mobility according to any one of claims 1 to 8 in an electrochemical energy storage device, characterized in that: The electrochemical energy storage device is a secondary battery.

10. Use of the positive electrode with high carrier mobility in an electrochemical energy storage device according to claim 9, characterized in that: The secondary battery is a lithium ion battery, a metal lithium secondary battery, a sodium ion battery or a potassium ion battery.

Citation Information

Patent Citations

  • Lithium manganese phosphate or lithium manganese silicate power cell, positive and negative pole manufacturing method thereof

    CN101504994A

  • Manufacturing method of sulfur-containing positive electrode and manufacturing method of solid-state lithium battery containing positive electrode

    CN107317009A

  • Carbon-doped lithium ferromanganese phosphate sulfur-supported lithium sulfur battery cathode material and preparation method thereof

    CN109148854A

  • Lithium ion battery positive electrode material, and preparation method and application thereof

    CN113937276A

  • Composite positive electrode slurry, lithium ion secondary battery and preparation method of lithium ion secondary battery

    CN114142003A